The Effect of Liquidity and Solvency on Stock Prices with Profitability as an Intervening Variable: Empirical Study on Pulp and Paper Companies Listed on the Indonesia Stock Exchange (2016-2023) - Alamsyah Saputri, Fitri Angraeni; Nurdin, Maryam; Muspa, Muspa (LP2M IBK Nitro, 2025)
This research aims to examine the influence of liquidity and solvency on share prices through profitability as an intervening variable in pulp and paper sector companies on the Indonesian Stock Exchange with a research period of 2 months starting from September 2024 to October 2024. The population in this study were all pulp and paper sector companies listed on the Indonesia Stock Exchange in 2016-2023. while the sample in this study was determined using purposive sampling and the number of samples used was six companies. so that the number of samples obtained in this study was 48 samples. This study uses data documentation, namely from the financial reports of the companies studied and can also be through the Indonesia Stock Exchange. The statistical method used to test the hypothesis uses the help of the partial least square application. The results of the analysis show that: 1) Liquidity has a negative effect on profitability in pulp and paper sector companies, 2) Solvency has a negative and significant effect on profitability in pulp and paper sector companies, 3) Liquidity has a positive effect on stock prices in pulp and paper sector companies, 4) Solvency has a positive effect on stock prices in pulp and paper sector companies, 5) Profitability has a positive and significant effect on stock prices in pulp and paper sector companies, 6) Liquidity has a negative effect on stock prices in pulp and paper sector companies through profitability as an intervening variable, 7) Solvency has a negative effect on stock prices in pulp and paper sector companies through profitability as an intervening variable.